Love hurts [videorecording (Blu-Ray)] - Murray, Matthew (Screenwriter); Stoddard, Josh; Passmore, Luke; Quan, Kế Huy, 1971-; DeBose, Ariana, 1991-; Wu, Daniel, 1974-; Shakir, Mustafa (Mustafa S.); Tipton, Lio, 1988-; Gigandet, Cam, 1982-; Darby, Rhys, 1974-; Eriksen, André; Lynch, Marshawn, 1986-; et al. (Universal, 2025)
Marvin Gable, a realtor working in the Milwaukee suburbs, where 'For Sale' signs bloom. Gable receives a crimson envelope from Rose, a former partner-in-crime that he had left for dead. She's not happy. Now, Marvin is thrust back into a world of ruthless hitmen, filled with double-crosses and open houses turned into deadly warzones. With his brother Knuckles, a volatile crime lord, hunting him, Marvin must confront the choices that haunt him and the history he never truly buried.